Keterpakaian dan relevansi Jurnal Agritech sebagai rujukan artikel jurnal ilmiah internasional terindeks Scopus - Sri Junandi (Jurnal Kajian Informasi dan Perpustakaan, 2018)
Universitas Gadjah Mada through its Publishing Agency (BPP) aims to improve the quality of scientific journals, among others through internationalisation by including them to reputable indexing institutions. One of the requirements of internationalisation of scientific journals is that the articles in the journal have been cited by other articles in reputable international journals. Another requirement is the use of primary reference resources by the article comes from relevant and new scientific journals and proceedings. This study aimed to (1) identify the usage of Jurnal Agritech as the reference in published articles in international scientific journals indexed by Scopus, and (2) examine the refereed themes (Jurnal Agritech) in the article themes (other reputable journals). The study used the descriptive research method with quantitative approach. Data collection was conducted in February - March 2017 at Gadjah Mada University Library. Study results showed that Jurnal Agritech was used as a reference in articles published by international scientific journals indexed by Scopus. From the eight international scientific journals, the number of referred articles in Jurnal Agritech was one to six articles. Overall, articles published in the eight international scientific journals indexed by Scopus have referred to literatures relevant to Jurnal Agritech. It is therefore important that Jurnal Agritech is enhanced through the internationalization program by including it in the indexing agency.